RANCANG BANGUN PENGENDALI PERALATAN ELEKTRONIK DENGAN KENDALI SUARA MENGGUNAKAN TEKNOLOGI INTERNET OF THINGS BERBASIS NODEMCU - Amelia Damayanti; Dody Wahjudi; Tri Watininggsih; Isra' Nuur Darmawan (Program Studi Teknik Elektro Universitas Peradaban, 2022)
Controlling electronic equipment at home is generally done manually, but with the development of technology in today's modern era, there are many innovations that give rise to various ways of controlling electronic equipment, for example by remote control using IoT technology, using smartphone applications , or by remote control. This research aims to create a modern electronic equipment control system using voice commands with Google Assistant and Blynk. This control system uses an application as a sender, using both Iot media and voice control, namely the Google assistant. These components are assembled into one and made a prototype with the aim of facilitating testing before being attached to the actual installation. After testing the hardware and software. The result is that the response speed after sending data from the two media has different timeframes, IoT media has a response that depends on the internet network used with an average turning on the lights and fans is 0.7 seconds, while using the Google assistant is 4.5 seconds. The system works well if it has good network quality. The use of voice control has a pronunciation limit of 5 commands and uses English. The control system when it is first turned on is not directly connected to the internet, so the user must turn on the hotspot first so that the system can be connected and can run.